Eksistensi Hak Tanah Ulayat Masyarakat Adat dalam Hukum Tanah di Indonesia - Yogatiyana, Nana; Hidayatullah, Mohammad Arief (ANWARUL, 2022)
The existence and position of land plays an important role in encouraging and developing the potential of available natural resources, that is why land is a very valuable asset of the nation and state. In carryng out activities and fulfilling their needs, customary law communities will not be separated from using customary land which is utilized and empowered to obtain agricultural products and food ingredients. This study aims to determine the existence of customary or ulayat land right in the land law system in indonesia, where this ulayat land needs to be regulated in indonesian positive law. The research method used is literature study, which is a systematic and explicit method for identifyng, evaluating, and synthezing research results that have been produced by researchers and practitioners.